The Effect of Aggregate Size and Resin Fraction on The Damping Capacity of Epoxy-Marble Composite - Hermana, Gita Novian; Kusnowo, Roni; Purwadi, Wiwik; Pradesar, Yusuf (Jurnal Bahan Alam Terbarukan, 2021)
The production of material with high precission and high complexity has been rapidly increasing in several industrial sector. The high accuracy is difficult to achieve during manufacturing due to vibration factors that influenced the final product of material. In this study the relationship between particle size and percentage of marble aggregate with epoxy resin on damping capacity was studied systematically. The Composite materials were fabricated by using conventional casting technique with 10, 25, and 50% volume fraction of resin and two marble aggregate groups with 0.5-0.7 mm and 1.4-2.0 mm in particle size. The casting process was using multilayer pouring technologies to prevent void formation. 10% epoxy resin-fine marble aggregate has very good vibration result with 0.003 mm in displacement, 0.23 mm/s in velocity, and 0.2 m/s2 in acceleration. The 10% epoxy resin-fine marble aggregate also has the best damping ratio among the composite due to the large specific area and porosity inside the marble material with value of 0.5%. The multilayer pour techniques for composite has been successfully adapted in this study to minimalize void/bubble formation inside and upperside of epoxy resin during the fabrication of composite. The secondary electron image of composite was observed that the marble aggregates and epoxy resin bonding are very good and no crack or void formation in the interface of the marble aggregate and epoxy resin.